PENGARUH WORKPLACE SPIRITUALITY TERHADAP KOMITMEN ORGANISASI PADA KARYAWAN PT SATRIA MANDIRI SEMESTA - Ivan Adriandiva Christian; Meily Margaretha (Departemen Manajemen, 2021)
Work is something that has become a necessity for everyone because by doing work a person can fulfil the needs for his/her life. Humans are also competing to work with their best ability in order to generate high income. However, when employees are too focused to get the high income, sometimes several points will go unnoticed, which is the meaning that is obtained or given after doing the job. Individuals who feel the workplace spirituality will commit greater commitment in their careers. Individuals will tend to keep their jobs and pursue the job as a career. Individuals who experience workplace spirituality will also contribute more and produce positive performance. This study aimed to reconfirm whether there is an influence that workplace spirituality toward organizational commitment. This research was conducted with sample of 50 employees of PT Satria Mandiri Semesta using online questionnaires and data was processed using simple regression statistical methods. The results showed that there is a positive effect of workplace spirituality toward organizational commitment by 12.5% and strengthened with a significance value of 0.012. One of the managerial implications can be applied in the company based on the results of the research is the company should maintain and even increase the workplace spirituality through training or activities that allow employees work and engage together.